What sentiments are generated in learning experiences with autonomous and multicultural engineering teams? - Rodríguez-Galván, Lilia Carolina; Ayala-Garcia, Ivo Netali; Juárez, Eduardo Daniel; Abdul Malik, Noreha; Nordin, Anis Nurashikin; Rodamporn, Somphop (IEEE, 2023)
Learning experiences with autonomous and multi-cultural teams are relevant for the future because the composition of the groups and engineering working environments are becoming more ethnically, culturally and linguistically diverse. This paper analyzes of the sentiments generated through learning experiences created for autonomous and multicultural teams. The generated knowledge is helpful for students, academicians and administrators to align expectations and improve management, execution and feedback in learning experiences of this kind. The data was gathered from students' logbooks and written feedback from academicians who participated in two implementations of a summer engineering program at three universities in Malaysia, Mexico and Thailand. The key findings are: 1) the sentiment journey patterns of students and lectures, 2) sentiments from lecturers are manifested in students weeks later, and 3) confidence is the sentiment with the greatest tonality in learning experiences among autonomous and multicultural teams in this learning context.